'Play responsibly': consumers' attention to and understanding of warning messages on scratch-off lottery tickets. Issue 3 (2nd September 2021) - Horn, Tori L.; Whelan, James P.; Li, Qian; McPhail, Abby; Meyers, Andrew W.; Majeed, Rimsha; Huette, Stephanie
ABSTRACT: To explore whether consumers see and understand warning messages on scratch-off lottery tickets, two laboratory observation studies were conducted. In the first study, 64 undergraduates were randomly assigned to either freely interact with a lottery ticket (i.e. minimal instruction condition) or search for information on the ticket related to gambling risks (i.e. message search condition) and then handed a lottery ticket. Approximately, one third failed to turn to the back of the ticket where warning messages were placed, and few participants accurately identified the messages. In the second study, 47 undergraduates were randomly assigned to either the minimal instruction condition or message search condition. Participants viewed computer images of the front and back of two lottery tickets while eye movement data were recorded. Analyses revealed that participants looked at the messages, but no more than other comparable areas of the tickets regardless of instructional condition. Generally, participants reported that 'Play Responsibly, ' was easy to understand, but did not 'teach them anything new.' Approximately 20% of participants correctly interpreted the overall odds of winning statement. These findings support the need to improve the placement and content of scratchcard warning messages to educate players about the risks associated with lottery play.